San Román de Hornija 1908: First Sales Attempts of the Central Panel from the Altarpiece of Archbishop Sancho de Rojas (BSAA arte, 2020)
Manuel Gómez-Moreno arrived to San Román de Hornija (Valladolid) in 1908 and he appreciated the importance of the panel-paintings that were kept in the cemetery chapel and another, the central one, already removed to the episcopal palace of Zamora to be sold. He, very worried, wrote to Senator Elías Tormo, who publicly denounced the case. We go through the vicissitudes of this ensemble from the collected letters from Gómez-Moreno and the first citation to the central panel-painting (1883), with the premonitory warning of Manuel Bartolomé Cossío, who already requested its removal to the Museo del Prado, as it ended up happening in 1928.
Keywords: San Román de Hornija (Valladolid); Museo del Prado; Gothic painting; Manuel Gómez-Moreno; Severiano Ballesteros; Elías Tormo; Francisco Antón; Manuel Bartolomé Cossío